2007
DOI: 10.1021/la0624283
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Silica Nanoparticles in Microemulsions

Abstract: Silica nanoparticles for controlled release applications have been produced by the reaction of tetramethylorthosilicate (TMOS) inside the water droplets of a water-in-oil microemulsion, under both acidic (pH 1.05) and basic (pH 10.85) conditions. In-situ FTIR measurements show that the addition of TMOS to the microemulsion results in the formation of silica as TMOS, preferentially located in the oil phase, diffuses into the water droplets. Once in the hydrophilic domain, hydrolysis occurs rapidly as a result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 19 publications
(16 reference statements)
2
124
1
1
Order By: Relevance
“…The properties of particles change as their size approaches the nanoscale which in turn provides a large surface area. A variety of nanoparticles like SiO 2 , Cu, TiO 2 , ZrO 2 , BaTiO 3 , BaZrO 3 , LiNbO 3 and Fe 2 O 3 are reported in literature (Finnie et al 2007;Qui et al 1999;Li and Wang 1999;Sundaram et al 2007;Niederberger et al 2004;Kang et al 1996). The two main types of the oxides of iron, i.e., magnetite Fe 3 O 4 and maghemite Fe 2 O 3 are considered to be of great interest due to their paramagnetic properties and thus are used in many fields.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of particles change as their size approaches the nanoscale which in turn provides a large surface area. A variety of nanoparticles like SiO 2 , Cu, TiO 2 , ZrO 2 , BaTiO 3 , BaZrO 3 , LiNbO 3 and Fe 2 O 3 are reported in literature (Finnie et al 2007;Qui et al 1999;Li and Wang 1999;Sundaram et al 2007;Niederberger et al 2004;Kang et al 1996). The two main types of the oxides of iron, i.e., magnetite Fe 3 O 4 and maghemite Fe 2 O 3 are considered to be of great interest due to their paramagnetic properties and thus are used in many fields.…”
Section: Introductionmentioning
confidence: 99%
“…This synthetic process takes more time than the Stöber method. However, the reverse microemulsion method can overcome the limitations of the Stöber method [25,[55][56][57] by producing silica nanoparticles with a uniform size distribution. Furthermore, this method can efficiently dope dye molecules into the silica nanoparticles.…”
Section: Reverse Microemulsion Methodsmentioning
confidence: 99%
“…Spherical glycylglycine templated silica particles were prepared with both acidic and basic pH sol-gel mixture and the diameter of the obtained particles was compared. Finnie et al [19] reported that for the microemulsion synthesis of silica particles, smaller particles were formed using acidic catalysis. Surprisingly, in our study it was found that in some cases smaller particles were obtained with basic pH.…”
Section: Phmentioning
confidence: 99%